Growth Differentiation Factor 15 (GDF-15): A Novel Biomarker Associated with Poorer Respiratory Function in COVID-19 - Leticia Alserawan; Patricia Peñacoba; Sandra Elizabet Orozco Echevarría; Diego Castillo; Esther Ortiz; Laura Martínez-Martínez; Esther Moga Naranjo; Pere Domingo; Ivan Castellví; Cándido Juárez; Anaís Mariscal (Diagnostics, 2021)
It is essential to find new biomarkers for severity stratification of patients with coronavirus disease (COVID-19). Growth differentiation factor 15 (GDF-15) is upregulated in pathological conditions that involve inflammation and/or oxidative stress. We determined circulating levels of GDF-15 and correlated them with clinical and laboratory parameters reflecting severity in 84 patients with COVID-19, finding that GDF-15 levels were higher in both patients than in 20 healthy controls and were higher in patients with poorer respiratory function. GDF-15 levels also correlated with interleukin-6, C-reactive protein, ferritin and D-dimer levels and with neutrophilia and lymphopenia. Of all the analysed biomarkers, GDF-15 showed the best area under the receiver operating characteristics curve in identifying patients with poor respiratory function. In conclusion, our data support GDF-15 as a biomarker associated with pulmonary impairment in COVID-19 and so can potentially be useful in stratifying COVID-19 cases by severity.